2018
DOI: 10.1002/aps3.1155
|View full text |Cite
|
Sign up to set email alerts
|

Finding the pond through the weeds: eDNA reveals underestimated diversity of pondweeds

Abstract: Premise of the StudyThe detection of environmental DNA (eDNA) using high‐throughput sequencing has rapidly emerged as a method to detect organisms from environmental samples. However, eDNA studies of aquatic biomes have focused on surveillance of animal species with less emphasis on plants. Pondweeds are important bioindicators of freshwater ecosystems, although their diversity is underestimated due to difficulties in morphological identification and monitoring.MethodsA protocol was developed to detect pondwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…So far, most eDNA studies have focused on monitoring animal species, and only recently has this powerful method been applied to tracking aquatic plants. Typically, the eDNA is further analysed either by using species specific qPCR or traditional barcoding applied to water [31] for tracking invading or threatened species, or using metabarcoding for water [62] or soil samples [63] for global ecosystem biodiversity monitoring. In this study we have developed a specific probe assay for eDNA detection of the aquatic plant E .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, most eDNA studies have focused on monitoring animal species, and only recently has this powerful method been applied to tracking aquatic plants. Typically, the eDNA is further analysed either by using species specific qPCR or traditional barcoding applied to water [31] for tracking invading or threatened species, or using metabarcoding for water [62] or soil samples [63] for global ecosystem biodiversity monitoring. In this study we have developed a specific probe assay for eDNA detection of the aquatic plant E .…”
Section: Discussionmentioning
confidence: 99%
“…Another study successfully tested eDNA detection of H . verticillata in north American rivers and lakes [34] and three studies detected eDNA where the species had not yet been observed [31, 34, 35]. Several laboratory mesocosm experiments have tested the changes in aquatic plant eDNA over time, during and after introduction, and with and without grazers [3234].…”
Section: Introductionmentioning
confidence: 99%
“…In general, assays can target one or a small number of target species using taxon‐specific primers and PCR, or can simultaneously characterize multiple species by generating metabarcodes. eDNA assays of aquatic vascular plants from water samples have so far been based exclusively on the former approach (Gantz, Renshaw, Erickson, Lodge, & Egan, 2018; Kuzmina, Braukmann, & Zakharov, 2018; Matsuhashi, Doi, Fujiwara, Watanabe, & Minamoto, 2016; Scriver, Marinich, Wilson, & Freeland, 2015). Although metabarcoding has been used to characterize terrestrial plant communities (Bell et al., 2016; Fahner, Shokralla, Baird, & Hajibabaei, 2016; Hawkins et al., 2015), it has not yet been applied to aquatic plant communities despite its potential as an effective approach for describing plant communities that may include alien species and species at risk.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, no single marker has revealed a barcoding gap, in which interspecific sequence divergence consistently exceeds intraspecific sequence divergence, across all plant taxonomic comparisons. ITS might be more likely to show a gap than the commonly used plastid markers (Gill et al., 2019; Kuzmina et al., 2018), although this can be influenced by factors such as the relatedness of the taxa being compared (Gill et al., 2019) and the biogeographic region under consideration (Mosa et al., 2019). There is a clear lack of consensus on the most useful markers for plant barcoding and metabarcoding.…”
Section: Introductionmentioning
confidence: 99%
“…Similar problems were found by Andújar et al (2018) and for macroinvertebrates. Incomplete reference databases have also been reported by several authors for different biotic groups, such as littoral hard bottom communities (Wangensteen et al 2018), macrophytes (Kuzmina et al 2018) and ichthyoplankton (Hubert et al 2015). In our work, we likely deflated the rate of families detected by metabarcoding because we did not trust hits below 90% similarity, a very conservative approach in terms of assignment.…”
Section: Comparison Between Morphology and Metabarcodingmentioning
confidence: 96%